The Influence of Service Quality, Consumer Satisfaction, and Punishment On Willingness To Pay Service Management Fees - Darmawan Ardiansyah; Teofilus Teofilus; Endi Sarwoko (Dinasti Publisher, 2024)
In developing a real estate area, the developer plans a new life after the handover of the units and creating a new good life, it must be supported by quality area management as well, so that residents feel the benefits of paying Service Management Fees. The purpose of this study is to provide a more complete picture of the effect of service quality, customer satisfaction, and punishment on willingness to pay Service Management Fees. Quality area management is the basic thing that residents in an area want, such as maintaining good facilities for infrastructure and public facilities, cleanliness, waste management, security that can provide a sense of security to residents, park / greening maintenance, clean water management, but to be able to create quality management certainly requires sufficient costs from the receipt of Service Management Fee payments. In addition to quality management, customer satisfaction can emerge over the purchase of property from brand famous developers, the handover of the time, good quality products, the premium service features usually reserved by hotel and apartments, the application of consumer services, a good relationship with consumers, the events of community, customer loyalty programs that can bring benefits for consumers. This research suggests that the quality of service dan customer satisfaction highly important influence the willingness to pay IPL and the other side punishment can not be moderating willingness to pay service management fees.